Design a reverted compound gear train - Azri Mohd Razak
This final year project is about designing a reverted compound gear for automotive use. The Honda EX5 Dream has been choosing for this design project. This motorcycle has 4 gears. The gearbox of this motorcycle is use reverted compound gear train which there is even number of shaft.